Wireless home automation system for multifunctional devices incorporating Internet of Things (IoT) - Pedro, Bruno (2021)
Home automation systems have been increasing in quantity and quality, throughout the world. The scientific community has been spending its resources to improve these systems, regarding their capabilities, accessibility and price. In this article, a low cost, home automation system, in the form of an experimental prototype is presented, focused in wireless communication and IoT (Internet of Things) structures. The result of the work developed was a capable prototype, adaptable to conventional electrical installations, with smart management capabilities regarding actuators of electric loads and sensor information utilization.